The Effect of Care Setting in the Delivery of High-Value Colon Cancer Care - Veenstra, Christine M. (Cancer, 2014)
BACKGROUND: The effect of care setting on value of colon cancer care is unknown. METHODS: A Surveillance, Epidemiology, and End Results (SEER)-Medicare cohort study of 6544 patients aged ≥66 years with stage IV colon cancer (based on the American Joint Committee on Cancer staging system) who were diagnosed between 1996 and 2005 was performed. All patients were followed through December 31, 2007. Using outpatient and carrier claims, patients were assigned to a treating hospital based on the hospital affiliation of the primary oncologist. Hospitals were classified academic or nonacademic using the SEER-Medicare National Cancer Institute Hospital File. RESULTS: Of the 6544 patients, 1605 (25%) received care from providers affiliated with academic medical centers. The unadjusted median cancer-specific survival was 16.0 months at academic medical centers versus 13.9 months at nonacademic medical centers (P<.001). After adjustment, treatment at academic hospitals remained significantly associated with a reduced risk of death from cancer (hazard ratio, 0.87; 95% confidence interval [95% CI], 0.82–0.93 [P<.001]). Adjusted mean 12-month Medicare spending was $8571 higher at academic medical centers (95% CI, $2340–$14,802; P =.007). The adjusted median cost was $1559 higher at academic medical centers; this difference was not found to be statistically significant (95% CI, −$5239 to $2122; P =.41). A small percentage of patients who received very expensive care skewed the difference in mean cost; the only statistically significant difference in adjusted costs in quantile regressions was at the 99.9th percentile of costs (P<.001). CONCLUSIONS: Among Medicare beneficiaries with stage IV colon cancer, treatment by a provider affiliated with an academic medical center was associated with a 2 month improvement in overall survival. Except for patients in the 99.9th percentile of the cost distribution, costs at academic medical centers were not found to be significantly different from those at nonacademic medical centers.